PERAN KUA DALAM BIMBINGAN KURSUS CALON PENGANTIN (SUSCATIN) DI KANTOR URUSAN AGAMA (KUA) DISTRIK SORONG KOTA - Arum, Muhamad Yumaizar; Suharmoko (Muadalah : Jurnal Hukum, 2024)
Islam has complete rules regarding marriage and family. Everyone who gets married needs to comply with these rules to ensure that the household that is fostered is always harmonious and peaceful and receives the grace of Allah. Islam itself has the concept of premarital guidance aimed at young men who are about to get married. The bride-to-be course (Suscatin) is one way to provide knowledge, understanding and skills to the bride-to-be about married or family life. Basically, suscatin is an effort made in the formation of a household so that the bride-to-be is able to apply psychological provisions and skills in dealing with household problems. In this research, one of the theories, namely Shertzer and Stone, guidance is a process of assistance shown to individuals to recognize themselves and their world. This is an implementation of the Decree of the Minister of Religion Number 517 of 2001, concerning the Organizational Arrangement of KUA District/District. (KUA) Sorong Kota District before the implementation of the marriage contract for the two brides must provide premarital guidance so that the bride and groom understand the purpose and purpose of the marriage. So that later or after becoming husband and wife, they know the rights and obligations of husband and wife.